2010
DOI: 10.1364/oe.18.002020
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of attosecond XUV pulses utilizing a broadband UV~VUV pumping

Abstract: We propose a simple scheme to characterize attosecond extreme ultraviolet (XUV) pulses. A broadband ultraviolet (UV) approximately vacuum ultraviolet (VUV) pump pulse creates a coherent superposition of atomic bound states, from which photoionization takes place by the time-delayed attosecond XUV probe pulse. Information on the spectral phase of the XUV pulse can be extracted from the phase offset of the interference beating in the photoelectron spectra using a standard SPIDER (spectral phase interferometry fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…By measuring the phase offset of the quantum beat appearing in the energy-resolved photoelectron signal as a function of time delay between the two-color pump and XUV pulses, the spectral phase of the XUV pulse is accurately retrieved using the standard SPIDER algorithm. Compared with the VUV SPIDER [15], the two-color SPIDER has a remarkable advantage in terms of the reconstruction accuracy and the experimental feasibility due to the use of a Ti:sapphire laser. In contrast to the commonly used methods, such as FROG-CRAB and XSPIDER, which rely on SFA in one way or another, the two-color SPIDER, as well as the VUV SPIDER and Cs SPIDER, has a more transparent reconstruction process since they do not require any approximations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…By measuring the phase offset of the quantum beat appearing in the energy-resolved photoelectron signal as a function of time delay between the two-color pump and XUV pulses, the spectral phase of the XUV pulse is accurately retrieved using the standard SPIDER algorithm. Compared with the VUV SPIDER [15], the two-color SPIDER has a remarkable advantage in terms of the reconstruction accuracy and the experimental feasibility due to the use of a Ti:sapphire laser. In contrast to the commonly used methods, such as FROG-CRAB and XSPIDER, which rely on SFA in one way or another, the two-color SPIDER, as well as the VUV SPIDER and Cs SPIDER, has a more transparent reconstruction process since they do not require any approximations.…”
Section: Resultsmentioning
confidence: 99%
“…In practice, the detection angle has a finite width around Θ 0 . In a recent paper we have shown that the spectral phase error introduced by the finite width of the detection around Θ 0 is rather small and can be safely neglected [15].…”
Section: Descriptionmentioning
confidence: 99%
See 2 more Smart Citations